Hematopoietic Stem Cell Protocols - Klug, Christopher A.; Jordan, Craig T.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2002)
Hematopoietic stem cells have an enormous clinical importance for bone marrow transplantation, hematopoietic gene therapy, solid organ transplantation, and somatic tissue regeneration. In Hematopoietic Stem Cell Protocols, a group of leading stem-cell investigators describe in detail the key laboratory methods for investigating this critically important cell type. Varied in scope, and richly detailed with step-by-step instructions and notes on the pitfalls to be avoided, these readily reproducible protocols apply hematopoietic stem cells isolated from mouse and human tissues of both embryonic and adult origin. The many approaches described employ not only molecular and cell biology techniques, but also animal model systems, and include hematopoietic stem cell expansion protocols and methods for the purification and genetic modification of stem cells. Many of the protocols are contributed by those researchers who first developed and introduced the procedures to the scientific community. Comprehensive and state-of-the-art, Hematopoietic Stem Cell Protocols offers both novice and experienced investigators alike an invaluable compendium of highly practical techniques for studying a wide variety of stem cell topics, including blood formation, blood-based disease, and such blood cancers as leukemia.
Isolation and Analysis of Hematopoietic Stem Cells from Mouse Embryos -- The Purification of Mouse Hematopoietic Stem Cells at Sequential Stages of Maturation -- Flow Cytometry and Immunoselection of Human Stem Cells -- Method for Purification of Human Hematopoietic Stem Cells by Flow Cytometry -- Noninvasive Measurement of Hematopoietic Stem Cell Cycling and Turnover by In Vivo Bromodeoxyuridine Incorporation -- Isolation and Characterization of Primitive Hematopoietic Cells Based on Their Position in the Cell Cycle -- Hematopoietic Colony-Forming Cells -- Long-Term Culture-Initiating Cell Assays for Human and Murine Cells -- The Cobblestone-Area-Forming Cell Assay -- CFU-S -- Intrathymic Injection for Analysis of T-Cell Progenitor Activity -- Quantitation of Murine and Human Hematopoietic Stem Cells by Limiting-Dilution Analysis in Competitively Repopulated Hosts -- Ex Vivo Expansion of Human and Murine Hematopoietic Stem Cells -- Hematopoietic Development of ES Cells in Culture -- Genetic Modification of Murine Hematopoietic Stem Cells by Retroviruses -- Retroviral Transduction of FACS-Purified Hematopoietic Stem Cells -- Retroviral-Mediated Transduction and Clonal Integration Analysis of Human Hematopoietic Stem and Progenitor Cells -- Production of Lentiviral Vector Supernatants and Transduction of Cellular Targets -- Reverse Transcriptase-PCR Analysis of Gene Expression in Hematopoietic Stem Cells -- Identification of Differentially Expressed Genes in Sorted Cell Populations by Two-Dimensional Gene-Expression Fingerprinting.
Keywords: Hematology; Hematology